The knowledge of nurses on self-management principles in heart failure and their role as patients' educators – a narrative review - Krówczyńska, Dorota (Journal of Education, Health and Sport, 2022)
Introduction and objective: Nurses have primary responsibility for delivering education for patients with heart failure (HF) based on the current knowledge and effective strategies for improving patients' self-management. This narrative review aimed to determine nurses' knowledge of self-management principles in HF, including their role as patients' educators. This narrative review was based on papers indexed in the following databases: PubMed, MEDLINE, CINAHL, Web of Science, and Scopus. The inclusion criteria comprised: full-length articles available in English, recent papers published between 2000 and 2022, studies addressing the topic of assessing nurses' knowledge of self-management in HF, and discussing the nurse's role as a self-management educator in HF. Description of the state of knowledge: The main role of HF nurse is optimizing the therapeutic process, coordinating patients' care, objective monitoring of signs and symptoms, follow-up observation and check-up visits, and education for self-care and self-management. Therefore, nurses should be adequately trained in the principles of HF self-management and must have access to appropriate information provided to patients. A proper nurses' knowledge of self-management principles of patients is a crucial component of chronic illnesses such as HF. Summary: The knowledge level of nursing professionals is far from satisfactory. Therefore, nurses need more in-depth learning and understanding of the subject of HF through educational interventions and postgraduate training courses. In addition, nurses should have specialized knowledge and gain adequate competence to educate HF patients.